Characteristics and causes of Irminger Water variability in the subpolar North Atlantic between 1993 and 2022 ... - Wiegand, Kevin Niklas ("Staats- und Universitätsbibliothek (SuUB) Bremen", 2023)
Irminger Water (IW) originates in the subtropical North Atlantic and is transported northeastward with the North Atlantic Current. It is located in the Irminger Sea and the boundary current system (BCS) off Greenland and Labrador. As the warmest and most saline water mass in this region, it impacts glacial melt and convection in the Irminger and Labrador Seas. This thesis focuses on analyzing temporal and spatial variability of IW using the ARMOR3D data set from 1993 to 2022. It adds to analyzing IW in an ocean reanalysis and different model simulations. Utilizing data from ship surveys to the west of Greenland (at eastern AR7W), a local validation of ARMOR3D is performed. Eastern AR7W exhibits IW hydrography and volume transport variability. Seasonal variability results from colder and fresher waters formed during winter convection in the Irminger and Labrador Seas. On multi-year time scales, subpolar gyre changes tied to the North Atlantic Oscillation lead IW volume transports at eastern AR7W by up to ...